2022
DOI: 10.1530/eor-21-0102
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the proximal interphalangeal joint of the finger – a systematic review

Abstract: Arthrodesis of the proximal interphalangeal (PIP) joint of the finger is an established procedure for advanced osteoarthritis. As there are different techniques of fusion, it seems necessary to evaluate the results. Primary outcome of this review was to evaluate different arthrodesis methods of the PIP joint and describe different numbers of non-unions. Secondary outcome was to evaluate time to consolidation. Respective complications, if mentioned, were listed additionally. The review process was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although all the used implants have proven themselves to be capable of fusing the PIP joint of the finger in several clinical studies—as shown in the systematic review of Millrose et al—some are used in special circumstances [ 12 ]. For example, plates—regardless of whether they are of a fixation or locking design—show a tendency to lead to tendon adhesions—especially when applied near or on a joint, which might impair the function of the hand [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all the used implants have proven themselves to be capable of fusing the PIP joint of the finger in several clinical studies—as shown in the systematic review of Millrose et al—some are used in special circumstances [ 12 ]. For example, plates—regardless of whether they are of a fixation or locking design—show a tendency to lead to tendon adhesions—especially when applied near or on a joint, which might impair the function of the hand [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leibovic et al, stated after a clinical study in 1994, that techniques with compression of the fusion site could provide more reliable results [ 23 ]. The primary nonunion rate was highest using Kirschner wires, intermediate using tension band wires, and lowest using Compression screws; in a systematic review on this topic, this assumption could not be proven [ 12 ]. One possible explanation was that when combining the techniques into an analysis of compression versus non-compression, more advanced techniques such as tension bands were included—which show a higher complication rate than the compression screw—and therefore no evidence could be found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint denervation for post-traumatic osteoarthritis has been shown to be effective for proximal interphalangeal joints with an improved numeric pain scale and disabilities of the arm, shoulder, and hand questionnaire [5]. In a painful joint with severe functional limitations, surgical treatment options include joint fusion [9], implant arthroplasty [9][10][11][12][13], and free vascularized joint transfer [14,15]. Arthrodesis, including K-wires, tension band wiring, plates, and headless compression screws, may provide excellent pain relief and stability for those joints in the end stage of osteoarthritis [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a painful joint with severe functional limitations, surgical treatment options include joint fusion [9], implant arthroplasty [9][10][11][12][13], and free vascularized joint transfer [14,15]. Arthrodesis, including K-wires, tension band wiring, plates, and headless compression screws, may provide excellent pain relief and stability for those joints in the end stage of osteoarthritis [9]. Nevertheless, the complete loss of joint motion may cause some functional limitations [16].…”
Section: Introductionmentioning
confidence: 99%